ANALYSING FACTORS DETERMINING SUGAR RETAIL PRICE - Ninuk Rahayuningrum; Wayan Susila; Tjahya Widayanti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2007)
Since 2002, the government of Indonesia (GOI) has imposed promoting and protective to the Indonesia sugar industry. The policies have caused a significant increase in domestic production and farmer welfare. However, the policies also caused the government cannot effectively control the domestic retail price, especially when sugar price in the international market is very high. With this problem, this study is aimed at analyzing factors that significantly determine retail sugar price that can be used as policy instrument to control the price. An econometric model was used to determining the factors and their effect on the retail price. The result of analysis show that farm gate proce reference determined by the GOI, distribution costs, sugar import price, and market competition level are four main factor determining the retail price, explaining around 84% of retail price behavior. The elasticity of the sugar retail price toward the change of the four factors lies between 0.026-0.566. These imply that the GOI can use these four factors and their related variables as policy instrument to control the price.